Combating psychological distress with psychedelics in cancer patients - Fatima, Syeda Zainab; Zaheer, Saba (Journal of the Pakistan Medical Association, 2022)
Cancer is the leading cause of death worldwide and being diagnosed with cancer can be the source of severe pain and emotional distress to patients. It is not uncommon to find symptoms of depression, anxiety, hopelessness, loss of will to live, and meaning of life. Mitchell et al, found that the symptoms of depression and anxiety are present among 30-40% of hospitalized cancer patients, and 70-90% of cancer patients experience significant pain 1. These symptoms are found to have further debilitating effects on patients which include, non-compliance to medications, decreased quality of life and social functioning, suicidal thoughts, and poor progression and outcomes of the disease. —Continue